Blockage pattern of longitudinal flow in Meniere's disease. (July 2013) - Takano, Sakurako; Iguchi, Hiroyoshi; Sakamoto, Hiramori; Yamane, Hideo; Anniko, Matti
Abstract Conclusion: In the present study, classification of the patterns of 3D CT images of the ductus reuniens (reuniting duct) (RD), saccular duct (SD), and endolymphatic sinus (ES) gave more precise information for assessing the pathological condition of Meniere's disease (MD) than our previous study. Objective: This study attempted to provide more detailed information on MD by classifying the patterns of 3D CT images of the RD, SD, and ES in patients with MD. Methods: We examined the ears of 62 patients with definitely diagnosed unilateral MD based on the criteria of the Committee on Hearing and Equilibrium of the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) using 3D CT. The 3D CT images of bony grooves of RD, SD, and ES (BRD, BSD, and BES) were classified into patterns according to aspects of their patency. Results: BRD could be classified into six types by assessing their patency defined using the criteria in this study. In the ears on the affected side of patients with MD, the BRD, BSD, and BES lost continuity in 3D CT images along their bony routes and were significantly different from normal healthy ears (p < 0.01). There were no significant differences among each stage of MD in the distributions of BRD and BES except for BSD.